Histological evaluation on burns wound healing treated with nenas (Ananas comosus spp.) and gelam (Melaleuca spp.) honey - Mohd Zohdi, Rozaini; Abu Bakar @ Zakaria, Md Zuki; Mohamed Mustapha, Noordin; Yusof, Norimah; Abdullah, Muhammad Nazrul Hakim (Universiti Putra Malaysia Press, 2004)
The efficacy of topical application of Malaysian honeys on burns wound healing in Sprague-Dawley rats was investigated on the basis of histological changes. A total of 45 Sprague Dawley male rats weighing 200-300 g were used in this study. Deep partial skin thickness burns were inflicted on the dorsal part of each animal. Two types of local honeys (nenas and gelam) were applied twice a day in a quantity of 0.5 ml for each application, while control animals received no treatment. The rats were serially euthanatized at 3, 7, 14, 21 and 28 days post treatment for histological study. Histological examination showed a significant decreased in the number of inflammatory cells and increased vascularity in the honey Gelam-treated wounds as compared to the honey Nenas-treated wounds and control group. This study showed that there was a significant acceleration of the dermal repair in wound healing treated with Gelam honey compared to control and honey Nenas-treated groups.